Endoscopic treatment of pancreaticopleural fistulas - Jagielski, Mateusz; Piątkowski, Jacek; Jackowski, Marek (Frontiers in Cellular and Infection Microbiology, 2022)
Introduction: Pancreaticopleural fistula (PPF) is a serious complication of acute and chronic pancreatitis. Objective: To evaluate the effectiveness of various endoscopic techniques for the treatment of patients with PPFs. Methodology: Prospective analysis of the results of endoscopic treatment of 22 patients with PPF due to pancreatitis was conducted at the Department of General, Gastroenterological, and Oncological Surgery, Ludwik Rydygier Collegium Medicum in Bydgoszcz, Nicolaus Copernicus University in Torun, between 2018 and 2021. Results: PPF was diagnosed in 22 patients (21 men and 1 woman; mean age 49.52 [30–67] years) with pancreatitis. In 19/22 (86.36%) patients, PPF communicated with the left pleural cavity and in 3/22 (13.64%) patients with the right pleural cavity. Chronic pancreatitis was diagnosed in 14/22 (63.64%) patients. Symptomatic pancreatic fluid collections were found in 15/22 (68.18%) patients with PPF (pancreatic pseudocyst in 11 and walled-off pancreatic necrosis in four patients). Endoscopic retrograde cholangiopancreatography was performed in 21/22 (95.45%) patients, confirming the diagnosis of PPF. All 21 patients underwent endoscopic sphincterotomy with prosthesis implantation in the main pancreatic duct (passive transpapillary drainage). In 1/22 (4.55%) patients, active transmural/transgastric drainage of the PPF was necessary due to inflammatory infiltration of the peripapillary region, precluding endoscopic pancreatography. Endoscopic transmural drainage was performed in all the 15 patients with pancreatic fluid collection. Clinical success was achieved in 21/22 (95.45%) patients. The mean total time of endotherapy was 191 (range 88–712) days. Long-term success of endoscopic treatment of PPFs during one year follow-up period was achieved in 19/22 (86.36%) patients. Conclusions: Endoscopic treatment is effective for managing post-inflammatory PPFs. The preferred treatment method is passive transpapillary drainage (prosthesis of the main pancreatic duct). If transpapillary drainage is not feasible, transmural drainage of the PPF remains the preferred method. Endoscopic transmural drainage leads to closure of the fistula canal in patients with pancreatic fluid collection complicated by PPF.